A study on the driving effects of digital trade development on total factor productivity growth and potential economic growth rate - Deng, Xitao (Edelweiss Applied Science and Technology, 2026)
This study investigates the driving effects of cross-border digital trade development on Total Factor Productivity (TFP) growth and potential economic growth rates, addressing the macroeconomic puzzle of rapid digital expansion coexisting with sluggish productivity growth—the contemporary “Solow Paradox.” The study constructs a theoretical framework integrating digital trade into the production function, employing comprehensive analysis of macro- and micro-level evidence from panel data across multiple economies. The research utilizes econometric methods including fixed-effects models and threshold effect analysis to examine transmission mechanisms. Digitalization exhibits a non-linear, U-shaped impact on productivity. Most firms remain below a critical digitalization threshold (approximately 0.1373), where adjustment costs outweigh efficiency gains. Infrastructure gaps, skill shortages, institutional rigidities, and fragmented cross-border data governance limit spillovers and concentrate benefits among frontier firms. The Solow Paradox reflects a sub-threshold trap rather than technological failure. Productivity gains from digital trade are conditional on complementary investments in infrastructure, human capital, institutional reform, and coherent data governance. Policymakers should prioritize digital infrastructure development, implement sequenced reform strategies, and address institutional frictions. Elevating the TFP of the bottom 90% of firms could potentially drive an 18% GDP increase over 6-8 years.